Origin of Electron Boomerang Stripes: Localized ULF Wave‐Particle Interactions. Issue 17 (31st August 2020) - Zhao, X. X.; Hao, Y. X.; Zong, Q.‐G.; Zhou, X.‐Z.; Yue, Chao; Chen, X. R.; Liu, Y.; Blake, J. B.; Claudepierre, S. G.; Reeves, G. D.
Abstract: Ultralow frequency (ULF) wave‐particle interactions play a significant role in the radiation belt dynamic process, during which drift resonance can accelerate and transport energetic electrons in the outer radiation belt. Observations of wave‐electron drift resonance are characterized by quasiperiodic straight or "boomerang‐shaped" stripes in the pitch angle spectrogram. Here we present an ULF wave event on 1 December 2015, during which both kinds stripes were observed by Van Allen Probes A and B, respectively. Using the time‐of‐flight technique based on the pitch angle dependence of electron drift velocities, the "boomerang‐shaped" stripes are inferred to originate from straight stripes at the time and location covered by Probe B. Given that straight stripes were indeed observed by Probe B, our observations strongly support the charged particle interacting with azimuthally localized ULF waves. A new method is provided to identify the location of ULF wave‐particle interaction on the basis of remote observations of electron flux modulations. Plain Language Summary: In the outer radiation belt, energetic electrons drift around the Earth with the periods of tens of minutes up to a few hours, which match the period of ultralow frequency (ULF) waves. Therefore, resonant wave‐particle interactions may occur during the electron drift motion, which are observationally characterized by quasiperiodic stripes, either straight or "boomerang shaped, " in the pitch angle spectrograms of electron fluxes. Here we observe, for the first time, the appearance of straight and "boomerang‐shaped" stripes at two Van Allen Probe locations, respectively. These observations support the scenario that the straight stripes are generated by localized wave‐particle drift resonance, and they are gradually distorted by the pitch angle‐dependent electron drift motion, to form "boomerang‐shaped" stripes outside the region of strong wave activity. This study also provides a new approach to identify the region of ULF wave‐particle interactions on the basis of remote observations of electron flux modulations. Key Points: ULF wave‐electron drift resonance can be characterized by quasiperiodic straight or boomerang stripes in the pitch angle spectragram Boomerang stripes evolve from straight ones after electrons drift away from the localized ULF wave‐particle interaction region We present a new approach to remotely identify the region of ULF wave activity, which is validated by two‐spacecraft measurements